2011
DOI: 10.1099/jmm.0.033456-0
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin-1 alpha produced by human T-cell leukaemia virus type I-infected T cells induces intercellular adhesion molecule-1 expression on lung epithelial cells

Abstract: The pathogenic mechanism of human T-cell leukaemia virus type I (HTLV-I)-related pulmonary disease, which involves overexpression of intercellular adhesion molecule-1 (ICAM-1) in lung epithelial cells, was investigated. The supernatant of HTLV-I-infected Tax

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 43 publications
0
10
0
Order By: Relevance
“…Our study demonstrated that individuals with TSP-HAM clinical form have a high frequency of lung injury. It is possible that the mechanism of developing lesions is an in situ inflammatory process, diagnosed through bronchoalveolar lavage fluid analysis that has been shown in previous studies, which could be more evident among the TSP-HAM individuals [ 18 , 19 , 33 , 34 ], with resultant induction of lung injuries, like bronchiectasis, fibrosis and scar lesions. Fibrosis itself could induce traction bronchiectasis in a cycle of chronic lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…Our study demonstrated that individuals with TSP-HAM clinical form have a high frequency of lung injury. It is possible that the mechanism of developing lesions is an in situ inflammatory process, diagnosed through bronchoalveolar lavage fluid analysis that has been shown in previous studies, which could be more evident among the TSP-HAM individuals [ 18 , 19 , 33 , 34 ], with resultant induction of lung injuries, like bronchiectasis, fibrosis and scar lesions. Fibrosis itself could induce traction bronchiectasis in a cycle of chronic lung injury.…”
Section: Discussionmentioning
confidence: 99%
“…[33], [34] It has been established that the Tax oncogene is an antigenic target of the adaptive immune response in HTLV-1 infected individuals. [35] Tax is also known to activate the IL-1α promoter, [36] several mouse models have demonstrated elevated levels of IL-1α in response to Tax expression, [13], [17], [37] and HTLV-1+ T cell clones produce high levels of IL-1α in culture. [38] Interestingly, Tax expression is largely restricted or absent in primary ATL cells [39], [40] and the same is true for IL-1α.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, HAM/TSP patients displayed lymphocytic inflammation [180][181][182] and changes in CT scan images [183][184][185]. Severe lung damage is predominantly observed in HTLV-1-associated inflammatory diseases such as HAM/TSP and uveitis due to the presence of high CD4 + CD25 + T lymphocytes, release of cytokines (i.e., IL-2, IL-12, and IFN-γ), inflammatory chemokines (i.e., MIP-1α and IP-10), and expression of ICAM-1 in the bronchioalveolar lavage fluid (BALF) [127,186]. The presence of lymphocytes in large quantities have shown to be positively correlated with high levels of FoxP3 mRNA in the BALF of patients with HTLV-1-related lung diseases [187].…”
Section: Evs In Pulmonary Diseasesmentioning
confidence: 99%